OTC derivatives and global economic activity: An empirical analysis - Gordon Bodnar; Jonathan Fortun; Jaime Marquez (Journal of Risk and Financial Management, 2017)
That the global market for derivatives has expanded beyond recognition is well known. What is not know is how this market interacts with economic activity. We provide the first empirical characterization of interdependencies between OECD economic activity and the global OTC derivatives market. To this end, we apply a vector-error correction model to OTC derivatives disaggregated across instruments and counterparties. The results indicate that with one exception, the heterogeneity of OTC contracts is too pronounced to be reliably summarized by our measures of economic activity. The one exception is interest-rate derivatives held by Other Financial Institutions.
Keywords: C1; 650; over the counter derivatives; economic activity; cointegration